Lichen Diversity and its Distribution Pattern in Tropical Dry Evergreen Forest of Guindy National Park (GNP), Chennai - Balaji, P.; Hariharan, G. N. (Indian Forester, 2004)
Quantitative ecological data suggested the impact of key site characters on lichens within the Tropical Dry Evergreen Forest at GNP. Twelve quadrats (each of 0.1 ha) were inventoried for lichen species diversity and their relationship with prominent site characters such as vegetation structure, tree density and host tree diversity were analyzed at GNP, Chennai. A total no of 31 species of lichens were found under 26 genera in 19 families in 9 Fungal Orders, recorded from 219 individuals of phorophytes in a total sample of 264 out of which 235 trees, 27 shrubs and 2 lianas of â‰¥ 3cm gbh. Strongest correlation emerged between tree density and host tree diversity on lichen distribution. Species like Arthopyrenia alboatra, Parmotrema saccatilobum, Strigula elegans, Tapellaria sp. and Verrucaria sp were found to be narrowly distributed in the park and specific to a single host.